THE DEVELOPMENT OF COLLABORATIVE MATHEMATICS LEARNING EMBEDDED WITH BALINESE CULTURAL PRINCIPLE - Made Manik Widayani; I Gusti Putu Suharta; I Made Ardana (Jurnal Pengajaran MIPA, 2019)
Learning collaboratively has been proven to be beneficial in learning mathematics. Unfortunately, studies have elicited obstacles in implementing collaborative learning, such as students’ behavior when engaging in collaborative learning. We address this problem by embedding local wisdom from Bali, namely Tri Hita Karana, within a learning handbook for studying polyhedron. Successful conceptual understanding after learning mathematics with the handbook showed potential merit of the handbook to be implemented in learning mathematics and students’ behavior while doing collaborative works also showed that embedding cultural context in learning could foster students’ collaboration skills.